Monetary policy normalization in the euro area - Daniel Privitera; Malte Rieth (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
The ECB announced in October 2018 that it would begin to cut back the amount of monthly asset purchases starting January 2018 while extending the duration of the purchases until at least September 2018. At it latest Governor's Council meeting in January 2019 it decided to remain on this track despite a sharp appreciation of the euro in the meanwhile. These steps were just two on a longer and potentially slippery path back towards standard monetary policy. Market turbulences like the so-called "Taper Tantrum", which followed the Fed's 2013 announcement that it was considering to cut back its asset purchasing program, have made central banks wary of the risks of premature or overly explicit announcements of monetary policy normalization. This article provides a short review of quantitative easing (QE) in the euro area since 2015 and of the debate about the right timing for terminating QE.
Keywords: 330